UFO-L: uma ontologia núcleo de aspectos jurídicos construída sob a perspectiva das relações jurídicas - Beccalli, Cristine Leonor Pereira Griffo (2018)
In the past decades, Law has turned to Computation in search of solutions for the representation of legal domain, for storage of large volumes of information and for retrieval of this information to generate knowledge to support decision-making. Among the several solutions proposed for representation of legal domain, we highlight legal ontologies, which propose the representation of a shared conceptualization of legal concepts and their relations. Those legal ontologies that represent generic legal concepts that can be used and reused in the construction of other ontologies or in legal modeling languages are called Legal Core Ontologies (LCOs). The approach of most LCOs is focused on legal norms. However, in this research, we opted for a different approach, namely, on basing the construction of our Legal Core Ontology on legal relations. Although both approaches bring benefits, the advantage of the latter is the possibility of making explicit of concepts and relations that are not evidenced in the former. In particular, the perspective of legal relations as a relation between agents who play legal roles and are in legal positions. In this context, the problem to be addressed lies in the gap between Computation and Law, i.e. in the problem of conceptual modeling applied to carving legal reality and how it is represented. The theoretical basis of this thesis is composed of two theories: Robert Alexy's Theory of Constitutional Rights and the Theory of Ontological Foundations for Structural Conceptual Models proposed by Giancarlo Guizzardi. The result of this investigation is an artifact called UFO-L and its catalog of modeling patterns, applied in ontological analyzes, in the modeling of legal domains and in the construction of visual nodelling languages for legal domain.